2019
DOI: 10.1002/anie.201902761
|View full text |Cite
|
Sign up to set email alerts
|

Design and Use of de novo Cascades for the Biosynthesis of New Benzylisoquinoline Alkaloids

Abstract: The benzylisoquinoline alkaloids (BIAs) are an important group of secondary metabolites from higher plants and have been reported to show significant biological activities. The production of BIAs through synthetic biology approaches provides a higher‐yielding strategy than traditional synthetic methods or isolation from plant material. However, the reconstruction of BIA pathways in microorganisms by combining heterologous enzymes can also give access to BIAs through cascade reactions. Most importantly, non‐nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“…In the initial screening, a variety of THIQs were prepared using Thalictrum flavum NCS ( Tf NCS), in high enantiomeric excesses ( ee s) where the single isomer is indicated, and purified. [ 11 , 16 , 17 ] The substrate panel (Figure 2 a ) included BIAs ( 1 – 5 ) and C‐1 substituted THIQs with linear aliphatic or cyclic moieties ( 6 – 11 ). BIAs lacking the catechol group on the isoquinoline scaffolds or those bearing a halide group ( 12 – 14 ) were also included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial screening, a variety of THIQs were prepared using Thalictrum flavum NCS ( Tf NCS), in high enantiomeric excesses ( ee s) where the single isomer is indicated, and purified. [ 11 , 16 , 17 ] The substrate panel (Figure 2 a ) included BIAs ( 1 – 5 ) and C‐1 substituted THIQs with linear aliphatic or cyclic moieties ( 6 – 11 ). BIAs lacking the catechol group on the isoquinoline scaffolds or those bearing a halide group ( 12 – 14 ) were also included.…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 , 14 , 15 , 16 ] The diversity of THIQs generated has been further extended by forming in vitro cascades with enzymes upstream of NCS. [17] In plant BIA biosynthesis, methyltransferase (MT) enzymes operate downstream of NCS to methylate norcoclaurine. [18] Such natural product methylations involve transfer of a methyl group from S ‐adenosylmethionine (SAM) to specific nucleophilic sites on the scaffold, and is widely associated with activation of the compound or improvement of its biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…253 Furthermore, NCS was combined with other enzymatic or chemical transformations as in vitro (chemo)-enzymatic cascades for the synthesis of THIQ analogues: (i) a carboligasetransaminase-NCS cascade to access chiral 1,3,4-trisubstituted THIQs; 254 (ii) an NCS-catalysed Pictet-Spengler reaction and Na 2 CO 3 -mediated cyclisation to afford (S)-trolline; 255 (iii) a network of tyrosinase, decarboxylase, transaminase and NCS for efficient synthesis of several natural and non-natural BIAs. 256 Besides NCS, another important C-C bond forming enzyme, BBE, has been explored for synthetic purposes, such as preparation of (S)-scoulerine and its analogues via kinetic resolution 257 or deracemization 258 of the corresponding THIQs, and enantioselective dealkylation of N-ethyl THIQs. 259 Given the importance of the chiral THIQ scaffolds, many other biocatalytic approaches (besides NCS and BBE in the BIA pathway) have also been developed.…”
Section: Alkaloidsmentioning
confidence: 99%
“…[5,7] In nature this condensation reactioni sc atalysed by enzymes called Pictet-Spenglerases, [8] which are sub-categorised according to their substrates. For instance, norcoclaurine synthases( NCSs) [9] prefer dopamine as amine substrate,w hile strictosidine synthases (STRs) [10] acceptt ryptamine and its derivatives, leadingt ob-carbolines as products. While for norcoclaurine synthases ab road scope of carbonyl substratesh as been reported, [9] it has only recently been shown that STRs accepts mall aliphatic aldehydes besides the natural, highly functionalized aldehyde secologanin (4c, Figure1)and itsa nalogues.…”
mentioning
confidence: 99%
“…For instance, norcoclaurine synthases( NCSs) [9] prefer dopamine as amine substrate,w hile strictosidine synthases (STRs) [10] acceptt ryptamine and its derivatives, leadingt ob-carbolines as products. While for norcoclaurine synthases ab road scope of carbonyl substratesh as been reported, [9] it has only recently been shown that STRs accepts mall aliphatic aldehydes besides the natural, highly functionalized aldehyde secologanin (4c, Figure1)and itsa nalogues. [10d] In contrastt ot he natural reaction of tryptamine (1)w ith secologanin( 4c), which gives the (S)-configured product, (S)-strictosidine, smalla ldehydes such as isovaleraldehyde led to the (R)-configured product.…”
mentioning
confidence: 99%